Initial orientation vs maintenance of attention: Relationship with the severity of dependence and therapeutic outcome in a sample of cocaine use disorder patients. (May 2021) - Fernández-Calderón, F.; Lozano, O.M.; Moraleda-Barreno, E.; Lorca-Marín, J.A.; Díaz-Batanero, C.
Highlights: Orientating and attention maintenance showed different patterns and relations. Cocaine AB is positively correlated with craving. Avoidance tendency on long exposure trials is observed in most severe patients. Relapse and abandonment is associated with AB in short stimulus exposure. Abstract: The visual probe paradigm allows for evaluating attentional bias (AB), distinguishing between approach vs avoidance patterns of attention and assessing two different processes when the exposure time to images is manipulated: initial orienting and maintenance of attention. The present study aimed to analyze the predictive capacity of these two processes for substance use disorder severity and therapeutic outcomes of patients with cocaine use disorder in treatment. The sample consisted of 70 outpatients who were starting treatment at a public service. AB was evaluated using a task based on the visual probe (VP) paradigm with images presented under two conditions: 200 ms vs 1000 ms. Cocaine and alcohol use disorder severity, craving, retention in treatment and relapse in consumption were recorded. Cocaine AB in the 1000 ms condition was negatively correlated with the cocaine use disorder severity (r = −0.26), whilst a positive correlation was found between cocaine craving and cocaine AB (r = 0.29). Alcohol use disorder severity negatively correlated with cocaine AB in the 200 ms condition (r = −0.24). Logistic regression analysis revealed that, after controlling for gender, age, and substance use disorder severity, cocaine AB in the 200 ms condition predicted dropout and relapse. Our results suggest that patients who adhere to treatment and remain abstinent tend to show avoidance in the 200 ms condition, with effect sizes of r  = 0.29 and 0.30 respectively. The results suggest that training in avoidance strategies could be a valuable way of maintaining adherence and abstinence, as well as improving control of craving.